Renpenning syndrome in a female. Issue 3 (16th December 2019) - Cho, Raymond Y.; Peñaherrera, Maria S.; Du Souich, Christele; Huang, Lijia; Mwenifumbo, Jill; Nelson, Tanya N.; Elliott, Alison M.; Adam, Shelin; ,; Eydoux, Patrice; Yang, Gui X.; Chijiwa, Chieko; et al.
Abstract: Renpenning syndrome (OMIM: 309500) is a rare X‐linked disorder that causes intellectual disability, microcephaly, short stature, a variety of eye anomalies, and characteristic craniofacial features. This condition results from pathogenic variation of PQBP1, a polyglutamine‐binding protein involved in transcription and pre‐mRNA splicing. Renpenning syndrome has only been reported in affected males. Carrier females do not usually have clinical features, and in reported families with Renpenning syndrome, most female carriers exhibit favorable skewing of X‐chromosome inactivation. We describe a female with syndromic features typical of Renpenning syndrome. She was identified by exome sequencing to have a de novo heterozygous c.459_462delAGAG mutation in PQBP1 (Xp11.23), affecting the AG hexamer in exon 4, which is the most common causative mutation in this syndrome. Streaky hypopigmentation of the skin was observed, supporting a hypothesized presence of an actively expressed, PQBP1 mutation‐bearing X‐chromosome in some cells. X‐inactivation studies on peripheral blood cells demonstrated complete skewing in both the proband and her mother with preferential inactivation of the maternal X chromosome in the child. We demonstrated expression of the PQBP1 mutant transcript in leukocytes of the affected girl. Therefore, it is highly likely that the PQBP1 mutation arose from the paternal X chromosome.